2022
DOI: 10.1097/md.0000000000031411
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic melatonin for delirium in critically ill patients: A systematic review and meta-analysis with trial sequential analysis

Abstract: Background: Up to 80% of patients in the intensive care unit (ICU) suffer from delirium. Studies on the preventative use of melatonin in the ICU have produced mixed results. We performed a systematic review and meta-analysis to evaluate whether early administration of melatonin reduces the prevalence of delirium in critically ill patients.Methods: We searched Medline, Embase, and the Cochrane Library for randomized controlled trials comparing melatonin or melatonin agonists to placebo in ICU setting. The popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
(152 reference statements)
0
5
0
4
Order By: Relevance
“…However, its efficacy in preventing delirium has not yet been well established. In their SRMA of 12 trials involving the use of melatonin/ramelteon, Yan et al ( 7 ) reported a significant decrease in the incidence of delirium in the experimental group. ( 15 ) However, a sensitivity analysis and a trial sequential analysis revealed that this conclusion may be due to a false-positive error.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, its efficacy in preventing delirium has not yet been well established. In their SRMA of 12 trials involving the use of melatonin/ramelteon, Yan et al ( 7 ) reported a significant decrease in the incidence of delirium in the experimental group. ( 15 ) However, a sensitivity analysis and a trial sequential analysis revealed that this conclusion may be due to a false-positive error.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, sua eficácia na prevenção do delirium ainda não foi bem estabelecida. Em sua revisão sistemática e metanálise com 12 estudos sobre o uso de melatonina ou ramelteona, Yan et al ( 7 ) relataram diminuição significativa na incidência de delirium no grupo experimental. ( 15 ) No entanto, uma análise de sensibilidade e uma análise sequencial de estudos revelaram que essa conclusão pode ser devida a um erro falso-positivo.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…As those guidelines multiple trials and systematic reviews have demonstrated a preventive effect of dex on delirium in both medical and surgical ICU patients [38,39,40 ▪▪ ,41], and a 2022 Intensive Care Medicine rapid practice guideline suggested use of dex as sedation for ventilated patients in the ICU as long as the benefit of decreased delirium was not outweighed by the adverse effects of bradycardia and hypotension [42]. Melatonin and the melatonin receptor agonist Ramelteon have shown promise, but larger analyses report mixed results and effects only in select populations [38,43,44 ▪ ]. The atypical antipsychotic quetiapine has also recently been supported by a few smaller trials, especially in the ICU population [38,45 ▪▪ ,46].…”
Section: Elderly Patients With Rib Fracturesmentioning
confidence: 99%